Exploring double diffusive oscillatory flow in a Voigt fluid - Vinod, Y.; Raghunatha, K. R.; Felemban, Bassem F.; Aly, Ayman A.; İnç, Mustafa; Rezapour, Shahram; Sangamesh (World Scientific Publ Co Pte Ltd, 2025)
This paper's goal is to investigate the oscillatory flow of double-diffusive convection in a Voigt fluid. We re-design the basic equations of the channel flow, which initially appear dimensional, in a dimensionless manner using non-dimensional variables. The oscillation technique transforms the governing equations into coupled ordinary differential equations (CODEs). We have derived the analytical expressions for velocity, temperature, and concentration distribution by solving the CODEs using the direct analytical method. The study focuses on how physical factors, like the thermal Grashof number, the solutal Grashof number, the Prandtl number, the Lewis number, and the Voigt fluid parameter, affect different aspects of flow, such as speed, temperature, concentration, rate of heat transfer, and mass transfer. Notably, the study finds that skin friction increases on both channel plates with increasing injection on the heated plate. The significance of double-diffusive oscillatory flow lies in its ability to improve heat and mass transfer rates, as well as its impact on pattern formation and stability, which influences a wide range of applications from engineering design to environmental studies.
Keywords: Double-diffusive convection; oscillatory flow; Voigt fluid